IMPLEMENTASI KEBIJAKAN PENGAWASAN PEMILIHAN UMUM (PEMILU) PARLEMEN DI NEGARA TIMOR-LESTE TAHUN 2012 - Agostinho Alves Dos Santos; Soesilo Zauhar; Siti Rochmah (Universitas Tribhuwana Tunggadewi, 2015)
Policy Implementation to Monitoring Parliament Election, supervised by the National General Election Commission KNPU (Comissão Nacional da Eleiçoês CNE), based the law No.5/2006 on Election Supervisory Agency. Monitoring general election of parliament, was held on July 7, 2012, with of goal choosing the leaders of 21 political parties and coalitions of parties, above preconditions parliament election with the use D'Hondt method application, that is; each of the political parties and coalitions parties, must the meet criteria of 3% or (12000) the voting results obtained, to seize the amount of 65 seats of the national parliament. Research was method used is descriptive research with a qualitative approach. Data collection techniques of observation, interviews and documentation. Data analysis of, using interactive model of, Miles, Huberman and field Saldana 2014. Findings are indicate that the field of policy implementation monitoring election of parliament, including implementation mechanisms, human resources, the electoral system, the nature of elections and democracy, the actors involved in implementation of the Parliament election. There are factors supporting and Policy Implementation to monitoring Parliament election. Supporting factor: The existence of a strong commitment the president KNPU / CNE. System Operating Procedure (SOP), which is structured. The existence of education and citizenship program. The existence Actualization System Data Base. Inhibiting factor: The increasing violation by political parties in campaign. Lack of limited human resource. Lack of understanding the symbols by political parties and the coalition parties.